2019
DOI: 10.1007/s40415-019-00547-w
|View full text |Cite
|
Sign up to set email alerts
|

Tupistra nutans Wall. root extract, rich in phenolics, inhibits microbial growth and α-glucosidase activity, while demonstrating strong antioxidant potential

Abstract: The current study was performed to determine the phenolic compounds composition, antioxidant and antimicrobial activity, and α-glucosidase inhibitory effect of the root extract of Tupistra nutans Wall., in order to validate its use in traditional medicine. HPLC-MS/MS analysis showed the presence of ferulic acid, protocatechuic acid, p-hydroxybenzoic acid, p-coumaric acid, salicylic acid, chlorogenic acid, caffeic acid, l-phenylalanine as the predominant phenolic compounds. The antioxidant potentials of T. nuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Taking into account the results of anti‐diabetic and anti‐tyrosinase assays, the findings may be related to phenolic in the leaf extracts. In studies conducted by several authors, a positive correlation was reported between the level of phenolics and the inhibition of these enzymes (Benabderrahim, Elfalleh, Sarikurkcu, & Sarikurkcu, 2019; Chung et al., 2019). In addition, some compounds such as chlorogenic acid, sinapic acid, and isorhamnetin were reported as inhibitory agents (Li, Habasi, Xie, & Aisa, 2014; Zheng et al., 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Taking into account the results of anti‐diabetic and anti‐tyrosinase assays, the findings may be related to phenolic in the leaf extracts. In studies conducted by several authors, a positive correlation was reported between the level of phenolics and the inhibition of these enzymes (Benabderrahim, Elfalleh, Sarikurkcu, & Sarikurkcu, 2019; Chung et al., 2019). In addition, some compounds such as chlorogenic acid, sinapic acid, and isorhamnetin were reported as inhibitory agents (Li, Habasi, Xie, & Aisa, 2014; Zheng et al., 2020).…”
Section: Resultsmentioning
confidence: 96%
“…The concentration and composition of phenolic compounds were identified in M. sacchariflorus using a liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) system, as described previously [ 111 ]. Pumps (Agilent 1200, Agilent Technologies, Palo Alto, CA, USA) and an autosampler (Agilent 1100 series, Agilent Technologies, Palo Alto, CA, USA) were coupled to an API 2000 series mass spectrometer (Applied Biosystems, ON, Canada) integrated to the LC system.…”
Section: Methodsmentioning
confidence: 99%
“…The phenolic compound concentration and composition were identified in L. chinense using a liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) system, as described previously by Chung et al [ 68 ]. Pumps (Agilent 1200, Agilent Technologies, Palo Alto, CA, USA) and an autosampler (Agilent 1100 series, Agilent Technologies, Palo Alto, CA, USA) coupled to an API 2000 series, mass spectrometer (Applied Biosystems, Ontario, Canada) were integrated to the LC system.…”
Section: Methodsmentioning
confidence: 99%